1986
DOI: 10.1159/000461557
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin in Chronic Inflammatory Diseases

Abstract: Several case studies are presented to illustrate the success of intravenous gammaglobulin (IVIG) therapy in ulcerative colitis, Crohn's disease, chronic anterior uveitis, herpes zoster, and relapsing genital herpes simplex. Hypothetical mechanisms explain the marked improvement of the chronic disorders, with particular emphasis on substitution of specific antibodies. The recently recognized heterogeneity of the major histocompatibility complex (MHC) is explored as one possible explanation for low and high resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Moreover, in primary immunodeficiency, intravenous immunoglobulin (IVIG) is a well-established therapy in the treatment of idiopathic thrombocytopenia, dermatomyositis and Kawasaki's disease. There are several case reports describing its successful usage in other conditions, but there are few controlled studies [16]. The mechanism of action is not known but regulation of complementary activity or interaction with receptor antibodies has been considered [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in primary immunodeficiency, intravenous immunoglobulin (IVIG) is a well-established therapy in the treatment of idiopathic thrombocytopenia, dermatomyositis and Kawasaki's disease. There are several case reports describing its successful usage in other conditions, but there are few controlled studies [16]. The mechanism of action is not known but regulation of complementary activity or interaction with receptor antibodies has been considered [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…9 The balance between inhibitory and activating Fc receptors may be critical in the understanding of immune function and regulation. 8,10,11 The infusion of IVIg may also result in the suppression of pathogenic cytokines, regulate the modulation of B and T cells, neutralize pathogenic auto antibodies, and interfere with complement aggregation at target tissues. 9,10 Although the data are limited, over 20 years of case reports, abstracts, review articles, and conference papers have reported clinical benefit of IVIg in IBD likely related to its antiinflammatory and immunomodulatory effects.…”
mentioning
confidence: 99%